Policy Analysis of the Establishment of the Koperasi Desa Merah Putih - Effendi, Rusfian; Deny, Muhammad; Kurniawan, Cristoporus Esandra Murta; Handoko, Irfan (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
In anticipation of Indonesia Emas 2045, the President of the Republic of Indonesia instructed the formation of the Merah Putih Village Cooperative, which aims to be an economic driver in achieving economic independence and food self-sufficiency. This research aims to analyze the policy for establishing the Merah Putih Village Cooperative. The method used is a SWOT analysis (Strengths, Weaknesses, Opportunities, Threats), which is employed to assess the success rate of the policy. This research utilizes secondary data, including government policies outlined in the Constitution, Presidential Instructions, Government Regulations, and data or information published in both print and online media. The results of this study indicate that Koperasi Merah Putih has strengths that can overcome weaknesses and threats, and capitalize on opportunities for the success of Koperasi Desa Merah Putih. Meanwhile, the conclusion of this study states that the establishment of the Merah Putih Cooperative is a strategic step that can accelerate the pace of Indonesia's economic growth. This policy is essential for improving the living standards of rural communities.